Mint Tea (Pennyroyal) Epileptic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs)
Severe epileptic encephalopathy and fulminant liver failure with cerebral edema in two infants given tea brewed from home-grown mint plant leaves are reported from the Departments of Pediatrics and Neurology, University of California, Davis Medical Ceneter, Sacramento.